Frost-acclimation of photosynthesis in overwintering Mediterranean holm oak, grown in Central Europe - Pflug, Ellen; Brüggemann, Wolfgang (International Journal of Plant Biology, 2012)
As a consequence of global change, forestry in Central Europe has to expect and be prepared for an increase of hot and dry summers in the near future. In two model plantations of the Mediterranean holm oak (Quercus ilex L.) in Central Europe (Rhine-Main basin) we tested its potential as a future forestry tree for drought-threatened stands by studying its overwintering strategy under harsh winter conditions. During prolonged frost periods, chronic photoinhibition was developed, which lasted until the end of the frost period. Nearly all plants survived minimum temperatures of - 16 to -18°C and their photosynthetic apparatus recovered completely during late winter. A detailed study of the temperature dependence of chlorophyll (chl) fluorescence parameters of the OJIP test revealed statistically significant correlations between minimum temperature and maximum quantum yield of primary photochemistry (Fv/Fm), absorption rate/reaction centre (ABS/RC), dissipation rate/reaction centre (DI0/RC) and electron transport rate/reaction centre (ET0/RC) as well as with the deepoxidation state (DES) of the xanthophyll pigments. The DES correlated with Fv/Fm, ABS/RC, DI0/RC and ET0/RC. It is concluded, that from the point of view of the winter hardiness of the photosynthetic apparatus, Q. ilex should be further investigated as a potential future forestry tree also for very dry and warm stands in Central Europe under the scenarios of climate change.
Keywords: chlorophyll fluorescence; ojip test; xanthophyll cycle

Photosynthesis and resource distribution through plant canopies - Niinemets, Uelo (PLANT CELL AND ENVIRONMENT, 2007)
Plant canopies are characterized by dramatic gradients of light between canopy top and bottom, and interactions between light, temperature and water vapour deficits. This review summarizes current knowledge of potentials and limitations of acclimation of foliage photosynthetic capacity (A(max)) and light-harvesting efficiency to complex environmental gradients within the canopies. Acclimation of A(max) to high light availability involves accumulation of rate-limiting photosynthetic proteins per unit leaf area as the result of increases in leaf thickness in broad-leaved species and volume: total area ratio and mesophyll thickness in species with complex geometry of leaf cross-section. Enhancement of light-harvesting efficiency in low light occurs through increased chlorophyll production per unit dry mass, greater leaf area per unit dry mass investment in leaves and shoot architectural modifications that improve leaf exposure and reduce within-shoot shading. All these acclimation responses vary among species, resulting in species-specific use efficiencies of low and high light. In fast-growing canopies and in evergreen species, where foliage developed and acclimated to a certain light environment becomes shaded by newly developing foliage, leaf senescence, age-dependent changes in cell wall characteristics and limited foliage re-acclimation capacity can constrain adjustment of older leaves to modified light availabilities. The review further demonstrates that leaves in different canopy positions respond differently to dynamic fluctuations in light availability and to multiple environmental stresses. Foliage acclimated to high irradiance respond more plastically to rapid changes in leaf light environment, and is more resistant to co-occurring heat and water stress. However, in higher light, co-occurring stresses can more strongly curb the efficiency of foliage photosynthetic machinery through reductions in internal diffusion conductance to CO2. This review demonstrates strong foliage potential for acclimation to within-canopy environmental gradients, but also highlights complex constraints on acclimation and foliage functioning resulting from light x foliage age interactions, multiple environmental stresses, dynamic light fluctuations and species-specific leaf and shoot structural constraints.
The following values have no corresponding Zotero field: pub-location: 9600 GARSINGTON RD, OXFORD OX4 2DQ, OXON, ENGLAND publisher: BLACKWELL PUBLISHING
Keywords: acclimation kinetics; age effects; foliage aggregation; leaf longevity; leaf structure; light acclimation; nitrogen content; support costs; tocopherol content; xanthophyll cycle

Photoprotection in evergreen Mediterranean plants during sudden periods of intense cold weather - García-Plazaola, J. I.; Olano, J. M. (Trees-Structure and …, 2003)
The photoprotective responses to an abrupt period of exceptional cold weather were studied in several Mediterranean evergreen species with different ecological requirements. The same pattern of response was observed in most of the species with little change in hydrophilic antioxidants (ascorbate and glutathione) and the carotenoid pool, an increase in the content of a -tocopherol, and a night retention of de-epoxidised xanthophylls (antheraxanthin and zeaxanthin). The accumulation of these xanthophylls correlated with a sustained decrease in maximal photochemical efficiency (Fv/Fm). This reduction in the rate of electron transport would reduce the production of superoxide in photosystem I, as well as the subsequent hydrogen peroxide and hydroxyl radical. Thereby if any transitory photooxidative stress is produced under these conditions it should be due mainly to the formation of singlet oxygen by triplet excited chlorophyll within the antenna. Since a-tocopherol is the main scavenger of singlet oxygen and lipid peroxy radicals, the large increase of this antioxidant within the species could be enough to compensate for the higher degree of photooxidative stress, playing an essential role in the survival of vegetation during the incidence of exceptional cold fronts in the Mediterranean region.
Keywords: a-tocopherol; antioxidants; photooxidative stress; xanthophyll cycle

How Plants Cope with Water Stress in the Field? Photosynthesis and Growth - Chaves, M. M.; Pereira, J. S.; MAROCO, J.; Rodrigues, M. L.; RICARDO, C. P. P.; OSÓRIO, M. L.; CARVALHO, I.; FARIA, T.; PINHEIRO, C. (Annals of Botany, 2002)
Plants are often subjected to periods of soil and atmospheric water deficit during their life cycle. The frequency of such phenomena is likely to increase in the future even outside today’s arid/semi‐arid regions. Plant responses to water scarcity are complex, involving deleterious and/or adaptive changes, and under field conditions these responses can be synergistically or antagonistically modified by the superimposition of other stresses. This complexity is illustrated using examples of woody and herbaceous species mostly from Mediterranean‐type ecosystems, with strategies ranging from drought‐avoidance, as in winter/spring annuals or in deep‐rooted perennials, to the stress resistance of sclerophylls. Differences among species that can be traced to different capacities for water acquisition, rather than to differences in metabolism at a given water status, are described. Changes in the root : shoot ratio or the temporary accumulation of reserves in the stem are accompanied by alterations in nitrogen and carbon metabolism, the fine regulation of which is still largely unknown. At the leaf level, the dissipation of excitation energy through processes other than photosynthetic C‐metabolism is an important defence mechanism under conditions of water stress and is accompanied by down‐regulation of photochemistry and, in the longer term, of carbon metabolism.
10.1093/aob/mcf10510.1093/aob/mcf105
Keywords: carbon assimilation; high temperature; Lupinus; photosynthesis; Quercus ilex; Quercus suber; stomatal functioning; Stress; Vitis vinifera; water-stress; xanthophyll cycle

Diurnal changes in antioxidant and carotenoid composition in the Mediterranean schlerophyll tree Quercus ilex(L) during winter - García-Plazaola, J. I.; Artetxe, Unai; BECERRIL, J. M.; Garcı, Ignacio (Plant Science, 1999)
Seasonal changes of pigment composition and antioxidant content were characterized in the Mediterranean evergreen holm oak (Quercus ilex L.). Higher contents of antioxidants and carotenoids, with a photoprotective role during winter, indicated that this period was highly stressful, so a study of diurnal changes in photosynthesis, pigments and carotenoids was conducted during January in sun and shade leaves. Sun and shade leaves were used to compare the effects due only to low temperature separate from those resulting from the interaction of light. During winter, a relatively high rate of CO2 ﬁxation on sun leaves represented an important sink for photosynthetic electrons contributing to the annual carbon balance of the plant. This high rate contrasted with a reduced Fv :Fm, even at predawn. This reduction was correlated with the accumulation of zeaxanthin at the expense of violaxanthin by de-epoxidation. Sun leaves were also protected by a higher concentration of antioxidants (ascorbate, glutathione and tocopherol) and carotenoids (except lutein epoxide). Ascorbate was 10–50-fold greater than the other antioxidants, indicating a central role in protection against photooxidative stress. Nevertheless those mechanisms were unable to avoid a loss of hydrophilic antioxidants (glutathione and ascorbate) and xanthophylls during the initial morning hours after dawn, indicating that the ﬁrst target of photooxidative damage was these molecules
Keywords: Holm oak; low-temperature stress; Mediterranean evergreens; photoinhibition; photoprotection; xanthophyll cycle